Relationship of environmental costs to product life cycle costs Applied in the General Company for Battery Industry - عبد الرزاق اسماء محمد (Journal of Economics and Administrative Sciences, 2012)
The relationship between costs of environment and costs of product life – cycle. Boubtlessly when the economical unit exercise their productive works, they lead to pollution in water, air and soil as well as all stages of product life- cycle from Rans Dstage, production stage, packaging stage and finally abandonment stage- Pollution causes environmental costs. Lgnoring or hiding environmental costs and no taking them in consideration with product cost lead to a wrong account of preduot cost. Therefore, environmental costs should be included and matched for all stages with in product costs to know which activities, processes or products that cause environmental costs that have importance in decision making.